Islamic nomocracy: from the perspectives of Indonesia, Spain and Russia - Wibowo, Sugeng; Dimyati, Khudzaifah; Absori, Absori; Wardiono, Kelik; Ramon, Tomás Mateo; Budiono, Arief; Lyandova, Vanka (Legality : Jurnal Ilmiah Hukum, 2023)
The Indonesian Islamic nomocracy paradigm has a long history and a cultural relationship with the national struggle that coincides with political and religious orientations. The Islamic nomocracy is inseparable from the relationship between Islam and the state rather than being linked to Islamic doctrine and power. This research employed the normative sociological method. It used a philosophical approach from Barbour’s paradigm of the relationship between religion and science and Habermas’ thought on religion in public spaces. This research strives to analyze the Islamic nomocratic paradigm pattern prior to Indonesian independence as a crucial stage that influences the following eras, namely the post-independence era, the Old Order Era, the New Order Era, and the Post-Reformation era up to now. This research aims to find the basics and the development of the Islamic nomocracy in the Indonesian legal system. The roots of the Islamic nomocracy legal thought in Indonesia can be traced to the pre-independence era. In the development of Islamic kingdoms, there was a dialog and integration process between the Islamic nomocracy and the kingdom government. After the War of Java, the conflict and independence pattern was formed. Before Indonesian independence, the Islamic nomocracy thought developed into Pan Islamism which tended to be conical to legal formalization through the caliphate system. After Indonesia’s independence, some of the Islamic nomocracy legal thought recognized the state as one of the legal systems in Indonesia besides customary law and positive law. Then, Indonesia became a partly-Islamic Legal State with a constant up-and-down relationship with the state. The authors also completed this paper with perspectives of Spain and Russia as both have been ruled under Muslim governance.